Blockchain Technology In Healthcare Services (Indian Journal of Cryptography and Network Security (IJCNS), 2024)
The recent ransomware attack on AIIMS (All India Institute of Medical Sciences) has highlighted internal system weaknesses in the healthcare sector, and blockchain technology has emerged as a potential solution to improve security and reduce the risk of future attacks. The decentralized blockchain technology makes it much more difficult for ransomware attackers to focus on a single point of failure. Additionally, blockchain technology provides recipients and data providers with the reassurance that their data has not been changed, enabling enterprises to have confidence and assurance in the integrity of their sensitive data. The sharing of data also restores control of data to its owners. The information is dispersed so that no one company can control it, yet it is still organized around the owner. Thamrin and Xu’s research paper proposes a framework for healthcare data storage that includes hospital, city, and state blockchain networks. The proposed system uses a private cloud, but the researchers recommend a hybrid cloud for improved efficiency and adaptability. This innovative approach has the potential to enhance healthcare systems’ data security, privacy, and accountability. However, a comprehensive analysis of the problem and an assessment of the potential effectiveness of blockchain technology is necessary before implementing any solutions.